The Role of Parents in the Use of Gadgets in Early Childhood - Novi Hidayati; Heny Djoehaeni; Badru Zaman (Early Childhood Education & Parenting, 2024)
This research is motivated by the importance of the role of parents, especially the role of the father which cannot be ignored. This study aims to see parental mediation given by fathers and mothers to children when using gadgets. The research method uses a qualitative approach with a case study research design. Data collection uses in-depth interviews and field notes involving three parents who have children aged 2-5 years in Harjamukti, Cirebon City which were analysed using grounded theory. The results of this study indicate that parents discuss, search, choose, and explain content that can be accessed in active mediation. Then, in the restriction mediation, parents provide restrictions on time, content, application, and distance. Co-viewing mediation is a way to increase closeness with the children and avoid excessive use of gadgets. Thus, parents collaborate on active mediation, restriction mediation, and co-viewing mediation to regulate and manage their children's use of gadgets.